Scoring abilities in the game of tennis - A pragmatic study of unique cases - Nowak, M.; Panfil, R. (Human Movement, 2012)
Many studies analyzing the game of tennis overlook assessing such variables as the pure ability to play the game or the skill needed to take an opponent by surprise. This can be quantified in terms of a player`s shot flexibility, variability, velocity, or by the conscious or intuitive adaptability one can possess towards anticipating return shots, how best to hit the ball in order to keep it in play, as well as the buildup of delivering a shot or in scoring a point. The aim of the study was to identify the ability to score points in tennis based on an original set of assessment criteria that were used to measure the different effective plays against an opponent. This included measuring the variability, spatial flexibility and variability of shots taken, as well as the willingness to make risky plays. Methods. The study analyzed the match play of two elite tennis players, Roger Federer and Novak Djokovic, who competed against one another in the final of the 2007 US Open and the semi-final of 2008 Australian Open. Video recording of the two games was used to score and measure the proposed criteria. Results. The study found numerous quantitative and qualitative aspects that could assess the performance of the players. This included measuring the variety, spatial flexibility and variability of shots taken, as well as the willingness to make risky plays. Shot variety, flexibility and variability, as well as the amount of risk taken during game play, were quantifiable in nature. Taking into account the high sporting level of the players, the obtained results are undoubtedly of considerable educational value. Conclusion. The results allow for the conclusion that the teaching process in tennis demands the introduction of significant modifications aimed at the rationalization of technique and the introduction of criteria that can measure player effectiveness.